Investigating the host-directed therapeutic potential of curdlan-functionalised PLGA nanoparticles in the treatment of intracellular Mycobacterium tuberculosis - Du Plessis, Su-Mari (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.